A kind of anti-corrosion ceramic material and preparation method thereof
By using polymer to coat α-Al2O3 micropowder in porous alumina ceramic materials, and by blending sintering and adding titanium dioxide and zirconia, the problems of insufficient dispersion, mechanical strength and corrosion resistance of the ceramic materials are solved, and higher flexural strength and acid-base corrosion resistance are achieved.
Patent Information
- Application Number
- CN202411646510.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-11-18
AI Technical Summary
Porous alumina ceramic materials have shortcomings in dispersion, mechanical strength and corrosion resistance.
Polyethylene glycol and phenylagenic anhydride to the α-Al2O3 micro powder are added to the polymerization reaction to form a carboxyl group-containing polymer, and blended and sintered by ball milling, aging and molding, and titanium dioxide and zirconia are used as sintering aids and corrosion-resistant modifiers to form a high-stability eutectic material.
The dispersion of α-Al2O3 micropowder is significantly improved, the flexural strength and acid-base corrosion resistance of ceramics are improved, and the corrosion quality loss rate in acid-base solutions is reduced.
Smart Images

Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic materials, in particular to an anti-corrosion ceramic material and a preparation method thereof. Background Art
[0002] Porous alumina ceramics are a kind of porous ceramic material with excellent performance, which has the advantages of high specific surface area, good heat resistance and strong seismic resistance. It is widely used in shock absorbing materials, thermal insulation materials, chemical sensors, etc. 2 O 3 The micro powder is mixed and sintered with a dispersant, a pore-forming agent, a sintering aid, etc. to obtain a porous alumina ceramic with excellent performance. The patent with publication number CN117430442A discloses a porous ceramic for gas sensor packaging that blocks ozone penetration, and its preparation method and application. The porous ceramic sheet obtained by sintering with calcined alumina, zinc oxide, iron oxide, chromium oxide, magnesium oxide, corn starch, methyl cellulose, polyethylene glycol, glycerol, polyvinyl alcohol, etc. as raw materials has good ozone barrier properties, hydrophobic air permeability and high temperature and humidity resistance. However, the porous ceramic sheet of the patent does not show good dispersibility, mechanical strength and corrosion resistance. Summary of the invention
[0003] The invention solves the problems of poor dispersibility, poor corrosion resistance and poor mechanical properties of porous alumina ceramics.
[0004] The technical solution provided by the present invention is: a method for preparing an anti-corrosion ceramic material:
[0005] (1) Add water and polyethylene glycol to the flask, stir to dissolve, then add α-Al 2 O 3 The micro powder, pyromellitic anhydride and pyridine are stirred to react, heated and dried to remove water, washed with petroleum ether and dried to obtain modified α-Al 2 O 3 Micro powder. The reaction formula is:
[0006] .
[0007] (2) Add water and 100 parts by weight of modified α-Al into the ball mill. 2 O 3micropowder, 1-2 parts by weight of titanium dioxide micropowder, 0.5-1.2 parts by weight of zirconium oxide, control the ball mill speed to 200-300r / min, and ball mill for 10-15min; pour the ball mill liquid into a sealed bag, and age it in an insulated box at 20-25℃ for 12-18h; then heat it to 90-100℃ in an oven, and heat and dry it for 2-3h; then place it in a mold, and use a molding machine to press it for 3-5min at a pressure of 20-30MPa to make a green body; finally, sinter it in a muffle furnace to obtain a porous alumina-based anti-corrosion ceramic material.
[0008] Preferably, in (1), the weights of polyethylene glycol, pyromellitic anhydride, and pyridine are α-Al 2 O 3 4-10%, 0.44-1.1%, 0.014-0.035% of the mass of micropowder.
[0009] Preferably, in (1), the reaction temperature is 40-50°C and the reaction time is 6-10h.
[0010] Preferably, in (2), the sintering process is to first heat the temperature to 350-400°C at a heating rate of 2-3°C / min in an air atmosphere, and keep the temperature for 30-40min; then heat the temperature to 800-950°C, and keep the temperature for 1.5-2h; and finally heat the temperature to 1200-1300°C, and keep the temperature for 2-2.5h.
[0011] The technical effect of the present invention is as follows: the present invention uses pyridine as a catalyst, polyethylene glycol and pyromellitic anhydride undergo polymerization reaction to generate a polymer containing carboxyl groups, and utilizes the carboxyl groups to react with α-Al 2 O 3 The surface of the micropowder undergoes coordination and other interactions, thereby 2 O 3 In-situ polymerization occurs on the surface of the micropowder, achieving the polymerization of the polymer to α-Al 2 O 3 The coating modification of micro powder is beneficial to improve the properties of α-Al 2 O 3 The dispersion of micro powder inhibits agglomeration and improves the mechanical properties of ceramics such as bending strength.
[0012] The modified α-Al 2 O 3 The polyethylene glycol-based polymer coated on the surface of the micropowder acts as a pore-forming agent. When sintered in an air atmosphere, the polymer undergoes thermal decomposition to form a rich and uniform pore structure in the ceramic matrix. The obtained alumina ceramic material maintains a relatively high porosity while still having good flexural strength.
[0013] The present invention uses titanium dioxide as a sintering aid and zirconium oxide as a corrosion-resistant modifier, and undergoes processes such as ball milling, aging, and molding. During the sintering process, zirconium oxide and α-Al 2 O 3 The formation of a highly stable eutectic is beneficial to improving the acid and alkali corrosion resistance of ceramic materials and reducing the corrosion mass loss rate of ceramic materials in acid and alkali solutions. DETAILED DESCRIPTION
[0014] The technical scheme in the embodiments of the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. The raw materials in the embodiments and comparative examples of the present application are all commercially available unless otherwise specified.
[0015] The α-Al of the present invention 2 O 3 The average particle size of the micro powder is 5.6 μm, the average particle size of the titanium dioxide micro powder is 200 nm, and the average particle size of the zirconium oxide is 600 nm.
[0016] Example 1
[0017] (1) Add 300 mL of water and 0.8 g of polyethylene glycol 2000 to a flask, stir to dissolve, and then add 20 g of α-Al 2 O 3 Micro powder, 90 mg of pyromellitic anhydride, 2.8 mg of pyridine, heated to 45 ° C, stirred for 6 hours, heated and dried to remove water, washed with petroleum ether, and dried to obtain modified α-Al 2 O 3 Micro powder.
[0018] (2) Add 100 mL of water and 100 g of modified α-Al into the ball mill. 2 O 3 Micropowder, 1 g titanium dioxide micropowder, 0.7 g zirconium oxide, control the ball mill speed to 250r / min, ball mill for 15 minutes; pour the ball mill liquid into a sealed bag, and age it in an insulated box at 25°C for 12 hours; then heat it to 90°C in an oven and heat and dry it for 3 hours; then place it in a mold, and use a molding machine to press it at a pressure of 25MPa for 5 minutes to make a green body; finally, in a muffle furnace, in an air atmosphere, at a heating rate of 2°C / , first heat it to 350°C, and keep it warm for 40 minutes; then heat it to 900°C, and keep it warm for 1.5 hours; finally heat it to 1300°C, keep it warm and sinter it for 2 hours to obtain a porous alumina-based anti-corrosion ceramic material.
[0019] Example 2
[0020] (1) Add 300 mL of water and 1.2 g of polyethylene glycol 2000 to a flask, stir to dissolve, and then add 20 g of α-Al 2 O3 The powder, 0.13g of pyromellitic anhydride, and 4.2mg of pyridine were heated to 50°C, stirred for 10h, heated and dried to remove water, washed with petroleum ether, and dried to obtain modified α-Al 2 O 3 Micro powder.
[0021] (2) Add 120 mL of water and 100 g of modified α-Al into the ball mill. 2 O 3 Micropowder, 1.5g titanium dioxide micropowder, 0.5g zirconium oxide, control the ball mill speed to 200r / min, ball mill for 15min; pour the ball mill liquid into a sealed bag, and age it in an insulated box at 20℃ for 18h; then heat it to 90℃ in an oven and heat and dry it for 3h; then place it in a mold, and use a molding machine to press it at a pressure of 30MPa for 3min to make a green body; finally, in a muffle furnace, in an air atmosphere, at a heating rate of 2℃ / , first heat it to 400℃, keep it warm for 30min; then heat it to 950℃, keep it warm for 1.5h; finally heat it to 1200℃, keep it warm for 2h to obtain a porous alumina-based anti-corrosion ceramic material.
[0022] Example 3
[0023] (1) Add 300 mL of water and 1.6 g of polyethylene glycol 2000 to a flask, stir to dissolve, and then add 20 g of α-Al 2 O 3 The powder, 0.18g of pyromellitic anhydride, and 5.7mg of pyridine were heated to 50°C, stirred for 10h, heated and dried to remove water, washed with petroleum ether, and dried to obtain modified α-Al 2 O 3 Micro powder.
[0024] (2) Add 120 mL of water and 100 g of modified α-Al into the ball mill. 2 O 3 micropowder, 1.5 g titanium dioxide micropowder, 0.85 g zirconium oxide, control the ball mill speed to 300r / min, ball mill for 10 minutes; pour the ball mill liquid into a sealed bag, and age it in an insulated box at 25°C for 12 hours; then heat it to 100°C in an oven and heat and dry it for 2 hours; then place it in a mold, and use a molding machine to press it at a pressure of 30MPa for 3 minutes to make a green body; finally, in a muffle furnace, in an air atmosphere, at a heating rate of 3°C / , first heat it to 400°C, keep it warm for 30 minutes; then heat it to 800°C, keep it warm for 2 hours; finally heat it to 1250°C, keep it warm and sinter it for 2.5 hours to obtain a porous alumina-based anti-corrosion ceramic material.
[0025] Example 4
[0026] (1) Add 400 mL of water and 2 g of polyethylene glycol 2000 to a flask, stir to dissolve, and then add 20 g of α-Al 2 O 3 The powder, 0.22g of pyromellitic anhydride, and 7mg of pyridine were heated to 40°C, stirred for 10h, heated and dried to remove water, washed with petroleum ether, and dried to obtain modified α-Al 2 O 3 Micro powder.
[0027] (2) Add 100 mL of water and 100 g of modified α-Al into the ball mill. 2 O 3 Micropowder, 2 g titanium dioxide micropowder, 1.2 g zirconium oxide, control the ball mill speed to 300r / min, ball mill for 10 minutes; pour the ball mill liquid into a sealed bag, and age it in an insulated box at 25°C for 12 hours; then heat it to 100°C in an oven and heat and dry it for 2 hours; then place it in a mold, and use a molding machine to press it at a pressure of 20MPa for 5 minutes to make a green body; finally, in a muffle furnace, in an air atmosphere, at a heating rate of 2°C / , first heat it to 400°C, keep it warm for 30 minutes; then heat it to 850°C, keep it warm for 2 hours; finally heat it to 1300°C, keep it warm for 2 hours, and obtain a porous alumina-based anti-corrosion ceramic material.
[0028] Example 5
[0029] (1) Add 400 mL of water and 1.8 g of polyethylene glycol 2000 to a flask, stir to dissolve, and then add 20 g of α-Al 2 O 3 The powder, 0.2 g of pyromellitic anhydride, and 6.2 mg of pyridine were heated to 45 ° C, stirred for 8 h, heated and dried to remove water, washed with petroleum ether, and dried to obtain modified α-Al 2 O 3 Micro powder.
[0030] (2) Add 100 mL of water and 100 g of modified α-Al into the ball mill. 2 O 3 Micropowder, 1.8 g titanium dioxide micropowder, 1 g zirconium oxide, control the ball mill speed to 300r / min, ball mill for 10 minutes; pour the ball mill liquid into a sealed bag, and age it in an insulated box at 25°C for 12 hours; then heat it to 100°C in an oven and heat and dry it for 2 hours; then place it in a mold, and use a molding machine to press it at a pressure of 25MPa for 5 minutes to make a green body; finally, in a muffle furnace, in an air atmosphere, at a heating rate of 2°C / , first heat it to 350°C, keep it warm for 40 minutes; then heat it to 850°C, keep it warm for 2 hours; finally heat it to 1300°C, keep it warm for 2 hours, and obtain a porous alumina-based anti-corrosion ceramic material.
[0031] Comparative Example 1
[0032] (1) Add 300 mL of water and 0.8 g of polyethylene glycol 2000 to a flask, stir to dissolve, and then add 20 g of α-Al 2 O 3 Micro powder, 2.8 mg pyridine, heated to 45 ° C, stirred for 6 hours, heated and dried to remove water, washed with petroleum ether, and dried to obtain modified α-Al 2 O 3 Micro powder.
[0033] (2) Add 100 mL of water and 100 g of modified α-Al into the ball mill. 2 O 3 Micropowder, 1 g titanium dioxide micropowder, 0.7 g zirconium oxide, control the ball mill speed to 250r / min, ball mill for 15 minutes; pour the ball mill liquid into a sealed bag, and age it in an insulated box at 25°C for 12 hours; then heat it to 90°C in an oven and heat and dry it for 3 hours; then place it in a mold, and use a molding machine to press it at a pressure of 25MPa for 5 minutes to make a green body; finally, in a muffle furnace, in an air atmosphere, at a heating rate of 2°C / , first heat it to 350°C, and keep it warm for 40 minutes; then heat it to 900°C, and keep it warm for 1.5 hours; finally heat it to 1300°C, keep it warm and sinter it for 2 hours to obtain a porous alumina-based anti-corrosion ceramic material.
[0034] Comparative Example 2
[0035] (1) Add 300 mL of water and 0.8 g of polyethylene glycol 2000 to a flask, stir to dissolve, and then add 20 g of α-Al 2 O 3 Micro powder, 90 mg of pyromellitic anhydride, 2.8 mg of pyridine, heated to 45 ° C, stirred for 6 hours, heated and dried to remove water, washed with petroleum ether, and dried to obtain modified α-Al 2 O 3 Micro powder.
[0036] (2) Add 100 mL of water and 100 g of modified α-Al into the ball mill. 2 O 3Micropowder, 1 g titanium dioxide micropowder, control the ball mill speed to 250r / min, ball mill for 15min; pour the ball mill liquid into a sealed bag, and age it in an insulated box at 25℃ for 12h; then heat it to 90℃ in an oven and heat and dry it for 3h; then place it in a mold, and use a molding machine to press it at a pressure of 25MPa for 5min to make a green body; finally, in a muffle furnace, in an air atmosphere, at a heating rate of 2℃ / , first heat it to 350℃, keep it warm for 40min; then heat it to 900℃, keep it warm for 1.5h; finally heat it to 1300℃, keep it warm for 2h to obtain a porous alumina-based anti-corrosion ceramic material.
[0037] The three-point bending method was used to test the flexural strength of alumina ceramic samples. The sample size was 40 mm × 4 mm × 3 mm and the loading rate was 0.5 mm / min.
[0038] The porosity of alumina ceramics was tested according to the method of GB / T 1966-1996.
[0039] The acid and alkali corrosion resistance of alumina ceramics was tested according to the method of GB / T 1970-1996. The medium of the acid corrosion test was a 20% mass fraction sulfuric acid solution. The medium of the alkali corrosion test was a 1% mass fraction sodium hydroxide solution. The boiling time was 1h. The mass loss method was used to calculate the percentage of mass reduction compared to the mass before corrosion, i.e. the corrosion mass loss rate.
[0040] The performance test results are shown in Table 1.
[0041] Table 1: Performance test results
[0042]
[0043] As shown in Table 1, in Examples 1-5, polyethylene glycol and pyromellitic anhydride are polymerized to generate a polymer containing a carboxyl group. 2 O 3 The surface of the micropowder undergoes coordination and other interactions, thereby 2 O 3 In-situ polymerization occurs on the surface of the micropowder, achieving the polymerization of the polymer to α-Al 2 O 3 The coating modification of micro powder is beneficial to improve the properties of α-Al 2 O 3 The dispersion of micro powder inhibits agglomeration and improves the mechanical properties of ceramics such as bending strength. 2 O 3The polyethylene glycol-based polymer coated on the surface of the micropowder is used as a pore-forming agent. When sintered in an air atmosphere, the polymer undergoes pyrolysis to form a rich and uniform pore structure in the ceramic matrix. The resulting alumina ceramic material has good bending strength while maintaining a high porosity. Titanium dioxide is further used as a sintering aid and zirconium oxide as a corrosion-resistant modifier. During the sintering process, zirconium oxide and α-Al 2 O 3 The formation of a highly stable eutectic is beneficial to improving the acid and alkali corrosion resistance of ceramic materials and reducing the corrosion mass loss rate of ceramic materials in acid and alkali solutions.
[0044] Compared with Example 1, the modified α-Al 2 O 3 When only polyethylene glycol is added, pyromellitic anhydride is not added. Polyethylene glycol does not contain carboxyl groups and is 2 O 3 The surface interaction of α-Al is low, making it difficult to achieve 2 O 3 The coating modification did not improve the α-Al 2 O 3 The dispersion of micropowders makes it difficult to effectively inhibit agglomeration. The porosity of the sintered ceramic material is low, and its bending strength and mechanical properties are poor.
[0045] Compared with Example 1, Comparative Example 2 does not add zirconium oxide, and the corrosion mass loss rate of the ceramic material in acid and alkali solutions after sintering is large, and the acid and alkali corrosion resistance is poor.
[0046] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, a person skilled in the art may make non-creative modifications to the present embodiment as needed, and such modifications shall be protected by the patent law as long as they are within the scope of protection claimed in the present application.
Claims
1. A method for preparing an anti-corrosion ceramic material, characterized in that: The preparation method is: (1) Add water and polyethylene glycol to a flask, stir to dissolve, then add α-Al2O3 powder, pyromellitic anhydride and pyridine, stir to react, heat and dry to remove water, wash with petroleum ether, and dry to obtain modified α-Al2O3 powder; (2) Add water, 100 parts by weight of modified α-Al2O3 powder, 1-2 parts by weight of titanium dioxide powder, and 0.5-1.2 parts by weight of zirconium oxide to a ball mill, and perform ball milling. Pour the obtained ball milling liquid into a sealed bag and age it in an insulated box; then heat and dry it in an oven; then place it in a mold and press it into a green body by a molding machine; finally, sinter it in a muffle furnace to obtain a porous alumina-based anti-corrosion ceramic material; Said (1), the weight of polyethylene glycol, pyromellitic anhydride, pyridine are 4-10%, 0.44-1.1%, 0.014-0.035% of the mass of α-Al2O3 powder; In the above (1), the reaction temperature is 40-50°C and the reaction time is 6-10h.
2. The method for preparing the anti-corrosion ceramic material according to claim 1, characterized in that: In the above (2), the rotation speed during ball milling is 200-300 r / min, and the time is 10-15 min.
3. The method for preparing the anti-corrosion ceramic material according to claim 1, characterized in that: In the above (2), the aging temperature is 20-25°C and the aging time is 12-18 hours.
4. The method for preparing the anti-corrosion ceramic material according to claim 1, characterized in that: In the above (2), the drying temperature is 90-100°C and the drying time is 2-3h.
5. The method for preparing the anti-corrosion ceramic material according to claim 1, characterized in that: In the above (2), the pressure when the green body is made is 20-30 MPa and the time is 3-5 min.
6. The method for preparing the anti-corrosion ceramic material according to claim 1, characterized in that: In (2), the sintering process is to first heat the temperature to 350-400°C in an air atmosphere at a heating rate of 2-3°C / min, and keep the temperature for 30-40min; then heat the temperature to 800-950°C and keep the temperature for 1.5-2h; and finally heat the temperature to 1200-1300°C and keep the temperature for 2-2.5h.
7. An anti-corrosion ceramic material obtained by the preparation method according to any one of claims 1 to 6.
Citation Information
Patent Citations
Ozone permeation blocking porous ceramic for gas sensor packaging as well as preparation method and application thereof
CN117430442A
Method for preparing porous aluminum oxide ceramic by virtue of polyurethane
CN109942314A
Method for preparing phase change latent heat material by modifying polyethylene glycol compound
CN110591655A